(untitled) (Analysis in Theory and Applications, 2017)
We give an existence result of the obstacle parabolic equations b(x,u)t -div(a(x,t,u, abla u))+div(φ(x,t,u)) =fin Q_T, where b(x,u) is bounded function of u, the term - div(a(x,t,u, abla u)) is a Leray-Lions type operator and the function φ is a nonlinear lower order and satisfy only the growth condition. The second term f belongs to L^1(Q_T). The proof of an existence solution is based on the penalization methods.